Selected acoustical parameters of highway noise barriers. (Research results digest (National Cooperative Highway Research Program), 1978)
"An NCHRP staff digest of the essential findings from the final report on NCHRP Project 3-26, "Investigation of Selected Noise Barrier Acoustical Parameters," by S. I. Hayek, J. M. Lawther, R. P. Kendig, and K. T. Simowitz, The Pennsylvania State University, University PArk, Pa."